Hydroxyapatite loaded copper-palladium diatomic catalyst as well as preparation method and application thereof
The hydroxyapatite-supported copper-palladium catalyst addresses the limitations of existing catalysts by enhancing activity and selectivity for methanol production from carbon dioxide, offering a cost-effective and scalable solution.
Patent Information
- Application Number
- CN202411192631.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-17
AI Technical Summary
Current copper-based catalysts for carbon dioxide hydrogenation to methanol suffer from poor hydrogenation activity, low methanol selectivity, and sintering issues, while palladium-based catalysts are expensive and require improved carbon dioxide adsorption and activation, and existing catalyst preparation methods are complex and unsuitable for large-scale production.
A hydroxyapatite-supported copper-palladium diatomic catalyst is prepared using an electrostatic adsorption method, with hydroxyapatite as a carrier, and optimized palladium and copper loading, calcination conditions, and atomic-level dispersion to enhance catalytic activity and selectivity.
The catalyst achieves high metal atom utilization rate, stability, and selectivity for methanol production under mild conditions, with a simple preparation process suitable for large-scale production, reducing material costs and environmental impact.
Smart Images

Figure CN119140133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic technology, and more specifically, to a hydroxyapatite-supported copper-palladium diatomic catalyst and a preparation method and application thereof. Background Art
[0002] Since the Industrial Revolution, the overuse of fossil fuels has led to a sharp increase in carbon dioxide emissions. In order to cope with the challenges posed by carbon dioxide to the environment and the economy, countries have actively introduced countermeasures, such as my country's "dual carbon" goal. Methanol, as a basic raw material for carbon-one chemistry, plays a vital role in chemical production. Carbon dioxide hydrogenation to methanol is an effective way to utilize carbon dioxide resources, and it is also an important way to produce methanol in the future, and it is expected to achieve chemical storage of renewable energy.
[0003] At present, the main metal catalysts used for the hydrogenation of carbon dioxide to methanol are copper-based, palladium-based, nickel-based, platinum-based, etc. Among the many metal catalysts, the most widely used is the copper-based catalyst, such as the Cu / ZnO / Al 2 O 3 Catalysts, but copper-based catalysts have poor hydrogenation activity, low methanol selectivity, and are easy to sinter in reducing and water-containing atmospheres. Precious metal catalysts have better low-temperature hydrogenation activity and stability and can replace copper-based catalysts, among which palladium-based catalysts have the best hydrogenation effect. However, metal palladium is expensive, scarce, and its adsorption and activation ability for carbon dioxide molecules needs to be improved. At the same time, the current preparation steps of metal catalysts are complicated and not suitable for large-scale production. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and to provide a hydroxyapatite-supported copper-palladium diatomic catalyst and its preparation method and application, which has a lower metallic copper and palladium loading and the highest (~100%) metal atom utilization rate. The carrier hydroxyapatite has a higher specific surface area, certain weak alkalinity and adsorption, and can catalyze the carbon dioxide hydrogenation reaction with high activity and high selectivity.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A hydroxyapatite-supported copper-palladium diatomic catalyst, comprising a carrier and an active component; the carrier is hydroxyapatite; the active component comprises active metal copper and active metal palladium; wherein the active metal palladium and the active metal copper are respectively supported on the carrier in atomic-level form; based on the total mass of the catalyst, the mass content of palladium is 0.01% to 5%, and the mass content of copper is 0.01% to 5%.
[0007] The present invention also discloses a method for preparing the hydroxyapatite-supported copper-palladium diatomic catalyst as described above, comprising the following steps:
[0008] (1) dissolving a copper metal precursor and a palladium metal precursor in deionized water to obtain a mixed solution;
[0009] (2) adding hydroxyapatite to the mixed solution, dispersing, filtering, washing and drying in sequence to obtain a catalyst precursor;
[0010] (3) calcining the catalyst precursor in an air atmosphere to obtain the hydroxyapatite-supported copper-palladium diatomic catalyst.
[0011] The present invention also discloses an application of the hydroxyapatite-supported copper-palladium diatomic catalyst as described above, or the hydroxyapatite-supported copper-palladium diatomic catalyst prepared by the preparation method as described above, in the hydrogenation of carbon dioxide to produce methanol.
[0012] Implementing the embodiments of the present invention will have the following beneficial effects:
[0013] The hydroxyapatite-supported copper-palladium diatomic catalyst provided by the present invention has a low metal loading and a high metal atom utilization rate (~100%). The carrier hydroxyapatite has a high specific surface area, certain alkalinity and adsorption, and is applied to the carbon dioxide hydrogenation to methanol reaction under mild conditions and efficiently catalyzes the formation of methanol. It has the advantages of high activity, high selectivity and catalyst stability during the reaction. The hydroxyapatite-supported copper-palladium diatomic catalyst provided by the present invention has low material cost, a stable catalyst structure during the reaction process, and is easy to reuse for a long time. The reaction process is environmentally friendly, and the technical and economic effects are significant, which is conducive to promotion.
[0014] The present invention adopts an electrostatic adsorption method to introduce transition metal copper and precious metal palladium to form a composite catalyst with a hydroxyapatite carrier. Among them, hydroxyapatite with a large specific surface area is selected as a carrier to improve the dispersibility of the active components in the catalyst, which is beneficial to ensure the stability of the catalyst; hydroxyapatite has certain adsorption and weak alkalinity, which is beneficial to the adsorption and activation of the reaction molecule carbon dioxide. At the same time, the present invention selects transition element copper and precious metal palladium with good compounding effect and catalytic hydrogenation activity, and optimizes the roasting temperature and time and regulates the atomic ratio of copper and palladium metals through continuous experiments, so that the prepared catalyst has the characteristics of low active component loading, good dispersibility, high utilization rate and stability; at the same time, the preparation method of the present invention has a simple process, is easy to operate, and is suitable for large-scale production, thereby overcoming the defects of the prior art such as the complex preparation process of metal catalysts, the low conversion rate and selectivity of catalytic carbon dioxide to methanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Electron microscopic images of the copper-palladium diatomic catalyst prepared in Example 1(a) and the catalyst prepared in Comparative Example 1(b).
[0016] Figure 2 This is a diagram of the preliminary performance evaluation results of Example 13. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0018] The invention discloses a hydroxyapatite-supported copper-palladium diatomic catalyst, which comprises a carrier and an active component; the carrier is hydroxyapatite; the active component comprises active metal copper and active metal palladium; wherein the active metal palladium and the active metal copper are respectively supported on the carrier in the form of atoms.
[0019] Furthermore, the hydroxyapatite-supported copper-palladium diatomic catalyst of the present invention has a palladium content of 0.01% to 5% by mass and a copper content of 0.01% to 5% by mass based on the total mass of the catalyst.
[0020] The present invention also discloses a method for preparing a hydroxyapatite-supported copper-palladium diatomic catalyst according to any embodiment of the present invention, which specifically adopts an electrostatic adsorption method and comprises the following steps:
[0021] (1) Dissolve a copper metal precursor and a palladium metal precursor in deionized water to obtain a mixed solution.
[0022] In a specific embodiment, the copper metal precursor includes one or more of copper nitrate, copper chloride, copper sulfate, copper acetate and copper acetylacetonate.
[0023] In a specific embodiment, the palladium metal precursor includes one or more of palladium nitrate, palladium chloride, tetraamminepalladium chloride, tetraamminepalladium nitrate and sodium chloropalladate.
[0024] (2) Adding hydroxyapatite to the mixed solution, dispersing, filtering, washing and drying in sequence to obtain a catalyst precursor.
[0025] In a specific embodiment, step (2) specifically includes: first drying the hydroxyapatite at 40°C to 800°C, adding the dried hydroxyapatite to the mixed solution, filtering and washing, and drying at 40°C to 200°C for 1h to 48h to obtain a catalyst precursor.
[0026] In a specific embodiment, the particle size of hydroxyapatite is 50nm to 1000nm. Preferably, the particle size of hydroxyapatite is 50nm to 800nm; more preferably, the particle size of hydroxyapatite is 60nm to 800nm; more preferably, the particle size of hydroxyapatite is 80nm to 750nm; most preferably, the particle size of hydroxyapatite is 600nm to 750nm.
[0027] In a specific embodiment, the mass ratio of hydroxyapatite, deionized water, copper metal precursor, and palladium metal precursor is 1:(1-10):(0.0001-0.05):(0.0001-0.05).
[0028] (3) The catalyst precursor is calcined in an air atmosphere to obtain a hydroxyapatite-supported copper-palladium diatomic catalyst.
[0029] In a specific embodiment, the calcination time is 1h to 48h; the calcination temperature is 100°C to 900°C. Preferably, the calcination temperature is 200°C to 800°C; the calcination time is 3h to 35h. More preferably, the calcination temperature is 200°C to 600°C; the calcination time is 5h to 20h. Most preferably, the calcination temperature is 500°C to 600°C; the calcination time is 5h to 15h.
[0030] The present invention also discloses an application of a hydroxyapatite-supported copper-palladium diatomic catalyst as in any embodiment of the present invention, or a hydroxyapatite-supported copper-palladium diatomic catalyst prepared by a preparation method as in any embodiment of the present invention, in the hydrogenation of carbon dioxide to produce methanol.
[0031] In a specific embodiment, in the process of producing methanol by hydrogenation of carbon dioxide, carbon dioxide and hydrogen are used as raw materials, and the reaction is carried out in a medium- and high-pressure fixed-bed reactor. The reaction temperature ranges from 100°C to 500°C, the reaction pressure is 0.1MPa to 5MPa, and the internal standard in the reaction gas is an inert gas argon or nitrogen with a volume fraction of 1% to 10%.
[0032] The following are specific embodiments
[0033] Example 1
[0034] 1) Cu(NO 3 ) 2 ·3H 2 O、Pd(NO 3 ) 2 (NH 3 ) 4 The precursors were dissolved in water at the same time to make their mass fractions 10% respectively. 0.25 mL of the precursor solution was added to 10 mL of deionized water and stirred for 0.5 h.
[0035] 2) 2 g of hydroxyapatite carrier with a size of about 600 nm and dried at 200° C. was added to the above solution and stirred for 3 h;
[0036] 3) After stirring, filter and wash;
[0037] 4) drying the product obtained in step 3) in an oven at 80° C. for 10 h;
[0038] 5) The product obtained in step 4) was calcined at 600° C. for 6 h in an air atmosphere with a heating rate of 5° C. / min. After natural cooling, a sample was taken out and recorded as CAT-1.
[0039] The results of electron microscopy characterization are as follows Figure 1 As shown in (a), no obvious copper metal and palladium metal particles were found, indicating that both are highly dispersed.
[0040] Comparative Example 1
[0041] The only difference between this comparative example and Example 1 is that the catalyst of this comparative example is prepared by sodium borohydride reduction method. The specific preparation method comprises the following steps:
[0042] 1) Cu(NO 3 ) 2 ·3H 2 O、Pd(NO 3 ) 2 (NH 3 ) 4 The precursor was dissolved in water to a mass fraction of 10%. 0.25 mL of the precursor solution was added to 10 mL of deionized water and stirred vigorously for 0.5 h.
[0043] 2) 2 g of hydroxyapatite carrier with a size of about 600 nm and dried at 200° C. was added to the above solution, and 10 mL of 1 mg / mL sodium borohydride aqueous solution was added dropwise under stirring at room temperature;
[0044] 3) stirring the product obtained in step 2) for 3 hours, filtering and washing, and then drying in an oven at 80° C. for 10 hours before taking out;
[0045] 4) The product obtained in step 3) was calcined at 600° C. for 6 h in an air atmosphere with a heating rate of 5° C. / min. After natural cooling, a sample was taken out and recorded as CAT-comparison-1.
[0046] Since sodium borohydride was added to reduce copper particles and palladium particles during the preparation process of this comparative example, when the copper and palladium loadings were the same as those in Example 1, the catalyst obtained in the end was mainly nanoparticles, as characterized by electron microscopy, such as Figure 1 As shown in (b), it is proved that copper metal and palladium metal nanoparticles exist obviously, but the dispersion is poor.
[0047] Example 2
[0048] 1) Cu(acac) 2 、Pd(acac) 2 The precursor was dissolved in benzene solvent to a mass fraction of 15%. 0.6 mL of the precursor solution was added to 20 mL of benzene solution and stirred for 1 h.
[0049] 2) 2 g of hydroxyapatite carrier with a size of about 200 nm and dried at 500° C. was added to the above solution and stirred for 24 h;
[0050] 3) After stirring, filter and wash;
[0051] 4) drying the product obtained in step 3) in an oven at 100° C. for 12 h;
[0052] 5) The product obtained in step 4) was calcined at 200° C. for 10 h in an air atmosphere at a heating rate of 3° C. / min. After natural cooling, the sample was taken out and recorded as CAT-2.
[0053] Example 3
[0054] 1) CuCl 2 ·2H 2 O、PdCl 2 The precursor was dissolved in water to make the concentration of copper and palladium metals 2 mg / mL. 1 mL of the precursor solution was added to 20 mL of deionized water and ultrasonicated for 15 min.
[0055] 2) 2 g of hydroxyapatite carrier with a size of about 300 nm and dried at 300° C. was added to the above solution and stirred for 12 h;
[0056] 3) After stirring, filter and wash;
[0057] 4) drying the product obtained in step 3) in an oven at 100° C. for 8 h;
[0058] 5) The product obtained in step 4) was calcined at 500° C. for 15 h in an air atmosphere with a heating rate of 10° C. / min. After natural cooling, the sample was taken out and recorded as CAT-3.
[0059] Example 4
[0060] 1)Cu(CH 3 COO 2 , PdCl 2 The precursor was dissolved in water to make the concentration of copper and palladium metals 2 mg / mL. 4 mL of the precursor solution was added to 3 mL of deionized water and ultrasonicated for 15 min.
[0061] 2) 10 g of hydroxyapatite carrier with a size of about 1000 nm and dried at 200° C. was added to the above solution and stirred for 5 h;
[0062] 3) After stirring, filter and wash;
[0063] 4) drying the product obtained in step 3) in an oven at 120° C. for 10 h;
[0064] 5) The product obtained in step 4) was calcined at 800° C. for 10 h in air atmosphere with a heating rate of 20° C. / min. After natural cooling, a sample was taken out and recorded as CAT-4.
[0065] Example 5
[0066] 1) CuSO 4 ·5H 2 O、Na 2 PdCl 4 The precursor was dissolved in water to make the concentration of copper and palladium metals 9 mg / mL. 1 mL of the precursor solution was added to 8 mL of deionized water and stirred evenly for 2 hours.
[0067] 2) 3 g of hydroxyapatite carrier with a size of about 100 nm and dried at 300°C was added to the above solution and stirred evenly for 24 hours;
[0068] 3) After stirring, filter and wash;
[0069] 4) drying the product obtained in step 3) in an oven at 150° C. for 10 h;
[0070] 5) The product obtained in step 4) was calcined at 800° C. for 16 h in an air atmosphere at a heating rate of 10° C. / min. After natural cooling, a sample was taken out and recorded as CAT-5.
[0071] Example 6
[0072] 1) CuSO 4 ·5H 2 O、Na 2 PdCl 4 The precursor was dissolved in , so that the concentration of metal copper and palladium was 3 mg / mL, 0.5 mL of the precursor solution was added to 3 mL of deionized water, and ultrasonicated for 15 min;
[0073] 2) Take 5 g of hydroxyapatite carrier with a size of about 200 nm and dried at 600°C, add it to the above solution and stir evenly for 12 hours;
[0074] 3) After stirring, filter and wash;
[0075] 4) drying the product obtained in step 3) in an oven at 60° C. for 20 h;
[0076] 5) The product obtained in step 4) was calcined at 600° C. for 10 h in an air atmosphere with a heating rate of 15° C. / min. After natural cooling, a sample was taken out and recorded as CAT-6.
[0077] Comparative Example 2
[0078] The only difference between this comparative example and Example 1 is that the active component only includes active metal palladium. The specific preparation process is as follows:
[0079] 1)Place Pd(NO 3 ) 2 (NH 3 ) 4 The precursor was dissolved in water to a mass fraction of 20%. 0.25 mL of the precursor solution was added to 10 mL of deionized water and stirred for 0.5 h.
[0080] 2) 2 g of hydroxyapatite carrier with a size of about 600 nm and dried at 200° C. was added to the above solution and stirred for 3 h;
[0081] 3) After stirring, filter and wash;
[0082] 4) drying the product obtained in step 3) in an oven at 80° C. for 10 h;
[0083] 5) The product obtained in step 4) was calcined at 600° C. for 6 h in an air atmosphere with a heating rate of 5° C. / min. After natural cooling, a sample was taken out and recorded as CAT-comparison-2.
[0084] Comparative Example 3
[0085] The only difference between this comparative example and Example 1 is that the active component only includes active metal copper. The details are as follows:
[0086] 1) Cu(NO 3 ) 2 ·3H 2 The O precursor was dissolved in water to a mass fraction of 20%. 0.25 mL of the precursor solution was added to 10 mL of deionized water and stirred for 0.5 h.
[0087] 2) 2 g of hydroxyapatite carrier with a size of about 600 nm and dried at 200° C. was added to the above solution and stirred for 3 h;
[0088] 3) After stirring, filter and wash;
[0089] 4) drying the product obtained in step 3) in an oven at 80° C. for 10 h;
[0090] 5) The product obtained in step 4) was calcined at 600° C. for 6 h in an air atmosphere with a heating rate of 5° C. / min. After natural cooling, a sample was taken out and recorded as CAT-comparison-3.
[0091] Example 7
[0092] The only difference between this embodiment and embodiment 1 is that the calcination temperature is 100° C. and the catalyst is denoted as CAT-7.
[0093] Example 8
[0094] The only difference between this embodiment and embodiment 1 is that the calcination temperature is 800° C. and the catalyst is denoted as CAT-8.
[0095] Example 9
[0096] The only difference between this embodiment and embodiment 1 is that the calcination temperature is 900° C. and the catalyst is denoted as CAT-9.
[0097] Example 10
[0098] The only difference between this embodiment and embodiment 1 is that the particle size of hydroxyapatite is 400 nm and the catalyst is denoted as CAT-10.
[0099] Embodiment 11
[0100] The only difference between this embodiment and embodiment 1 is that the particle size of hydroxyapatite is 950 nm and the catalyst is denoted as CAT-11.
[0101] Comparative Example 4
[0102] The only difference between this comparative example and Example 1 is that the loading amount of active metal palladium is 10%; the loading amount of active metal copper is 10%, and the catalyst is recorded as CAT-comparative-4.
[0103] Example 12
[0104] The performance of the catalyst prepared above was evaluated on a high-pressure fixed bed. 500 mg of the prepared copper-palladium diatomic catalyst and 500 mg of 300-mesh quartz sand were added to the reaction tube and mixed evenly. The raw gas components were: carbon dioxide gas 10 ml / min, hydrogen 30 ml / min, internal standard argon 1.5 ml / min, reaction pressure 3 MPa, reaction temperature 240°C. The specific reaction results are shown in Table 1.
[0105] Table 1 Catalytic performance of carbon dioxide hydrogenation to methanol in the examples and comparative examples
[0106]
[0107]
[0108] Embodiment 13
[0109] The performance of the catalyst prepared in Example 1 was evaluated in a high-pressure fixed bed reactor. 500 mg of the prepared copper-palladium diatomic catalyst and 500 mg of 200-mesh quartz sand were added to the reaction tube and mixed evenly. The raw gas components were: 10 ml / min of carbon dioxide gas, 30 ml / min of hydrogen, 1.5 ml / min of internal standard argon gas, and the reaction pressure was 3 MPa. The catalyst was tested for activity at 220-280°C, and then 280°C was selected for stability test. The results are as follows: Figure 2 It can be seen that the catalyst has high activity, methanol selectivity and good stability.
[0110] In summary, the present invention adopts hydroxyapatite with a large specific surface area, certain alkalinity and adsorption as a carrier through an electrostatic adsorption method, introduces transition element copper and precious metal palladium with good compounding effect and catalytic hydrogenation activity to compound with the carrier, and optimizes the calcination temperature and time through continuous experiments, and reasonably regulates the atomic ratio of copper and palladium metals. The prepared catalyst has the characteristics of low active component loading, good dispersibility, high metal atom utilization rate (~100%) and stability; it is applied to the carbon dioxide hydrogenation to methanol reaction, can efficiently catalyze the production of methanol under relatively mild conditions, and has the advantages of high activity, high selectivity and catalyst stability in the carbon dioxide hydrogenation reaction process.
[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A hydroxyapatite-supported copper-palladium diatomic catalyst, characterized in that: The catalyst comprises a carrier and an active component; the carrier is hydroxyapatite; the active component comprises active metal copper and active metal palladium; wherein the active metal palladium and the active metal copper are respectively loaded on the carrier in atomic-level form; based on the total mass of the catalyst, the mass content of palladium is 0.01% to 5%, and the mass content of copper is 0.01% to 5%.
2. A method for preparing the hydroxyapatite-supported copper-palladium diatomic catalyst as claimed in claim 1, characterized in that: The following steps are involved: (1) dissolving a copper metal precursor and a palladium metal precursor in deionized water to obtain a mixed solution; (2) adding hydroxyapatite to the mixed solution, dispersing, filtering, washing and drying in sequence to obtain a catalyst precursor; (3) calcining the catalyst precursor in an air atmosphere to obtain the hydroxyapatite-supported copper-palladium diatomic catalyst.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the hydroxyapatite, deionized water, copper metal precursor and palladium metal precursor is 1:(1-10):(0.0001-0.05):(0.0001-0.05).
4. The preparation method according to claim 2, characterized in that: In step (2), the drying temperature is 40° C. to 200° C., and the drying time is 1 h to 48 h.
5. The preparation method according to claim 2, characterized in that: In step (2), the particle size of the hydroxyapatite is 50 nm to 1000 nm; The hydroxyapatite is obtained through pretreatment, and the pretreatment temperature is 40°C to 800°C.
6. The preparation method according to claim 2, characterized in that: In step (3), the calcination time is 1 h to 48 h; the calcination temperature is 100° C. to 900° C.
7. The preparation method according to claim 6, characterized in that: In step (3), the calcination temperature is 200° C. to 600° C.; and the calcination time is 5 h to 20 h.
8. The preparation method according to claim 2, characterized in that: In step (1), the copper metal precursor includes one or more of copper nitrate, copper chloride, copper sulfate, copper acetate and copper acetylacetonate; The palladium metal precursor includes one or more of palladium nitrate, palladium chloride, tetraamminepalladium chloride, tetraamminepalladium nitrate and sodium chloropalladate.
9. Use of the hydroxyapatite-supported copper-palladium diatomic catalyst as claimed in claim 1, or the hydroxyapatite-supported copper-palladium diatomic catalyst prepared by the preparation method as claimed in any one of claims 2 to 8 in the hydrogenation of carbon dioxide to methanol.
10. The use according to claim 9, characterized in that: In the process of producing methanol by hydrogenation of carbon dioxide, the reaction temperature is 100°C to 500°C, the reaction pressure is 0.1MPa to 5MPa, and the internal standard in the reaction gas is an inert gas with a volume fraction of 1% to 10%.
Citation Information
Patent Citations
Method for preparing p-dioxanone from diethylene glycol and catalyst thereof
CN112724122A
Catalyst for preparing methanol through carbon dioxide hydrogenation, and preparation method and application thereof
CN113976126A
Zinc-zirconium catalyst for preparing methanol through thermal reduction of CO2 and preparation method of zinc-zirconium catalyst
CN117942990A
Cited By
Transition metal modified nano HAP catalyst as well as preparation method and application thereof
CN120733762A
Metal palladium immobilized hydroxyapatite composite catalyst as well as preparation method and application thereof
CN121042066A
Composite catalyst for oil refining alkaline residue treatment and preparation method thereof
CN122098626A
